(untitled) (Research, Society and Development, 2023)
Pressure injuries have become an indicator of the quality of care, given that they can be avoided, and their prevention has become a challenge for the multidisciplinary team, especially for nursing. In this sense, the study aims to describe, in the light of the literature, nursing actions regarding the prevention and treatment of pressure injuries in the intensive care unit. This is a literature review with a qualitative approach of an exploratory nature, through bibliographical research. For the development of the research, the national and international research databases available in the VHL (Virtual Health Library) were chosen in an integrated way with the Nursing Database (BDENF), and Latin American and Caribbean Literature on Life Sciences. Health (LILACS) and Google scholar. It is concluded that there is an extreme need for improvement of professionals on the subject, given that many articles brought the lack of knowledge as a constant problem in studies, an elaboration of protocols for recording and evaluating injuries based on evidence and scientific studies, It is also up to unit managers to invest more in professional training through continuing education, thus bringing more confidence to professionals to prevent and treat this common problem in health services.